Ideology in space production: mega-events as diffusion agents of the (neo)liberal ideology - Viana, Lucio Hanai Valeriano (Pontifícia Universidade Católica de São Paulo, 2019)
This work aims to examine the ideological aspects that permeate public policies and their relationship to urban spaces. It is based on the premise that mega-events, given their magnitude, have the potential for acting as diffusion agents of urban models. Relations of power and interests that direct the production of the urban space were analyzed to elucidate the urban characteristics associated with the accomplishment of mega-events. The work found that the strategies to hold mega-events are markedly targeted at the interests of the real estate market and are based on marketing strategies broadly represented by the neoliberal ideology.